Synthesis of N-heterocycles and building blocks using multicomponent, photochemical and electrochemical approaches - Bartolomeu, Aloisio de Andrade (2020)
Multicomponent reactions and protocols mediated by light and electrochemistry are powerful tools for modern organic synthesis. Moreover, they obey several principles of green chemistry such as atom economy, catalysis, waste reduction, energy efficiency, mild reaction conditions, etc. Therefore, the development of new synthetic methodologies employing these powerful tools is highly desirable and challenging. Chapter 1 describes the efficiency of NbCl5 for the promotion of MCRs between 4-formylphthalonitrile, anilines, and phenylacetylenes through a pericyclic hetero-Diels-Alder process. This multicomponent approach exhibited a wide substrate scope and, to demonstrate the versatility of the phthalonitrile library, we synthesized and characterized three new phthalocyanine derivatives. Chapter 2 covers a metal-free methodology for the photoarylation of pyridines and other heterocycles (such as quinoline and quinoxaline) with aryldiazonium salts in water using a homemade photoreactor. This photochemical approach displayed a broad scope regarding the diazonium salt component and further mechanistic investigations support a mechanism through an EDA complex. Finally, chapter 3 outlines the synthesis of sulfonyl fluorides through electrochemical oxidative coupling of thiols and potassium fluoride. This approach also showed a wide substrate scope, including a variety of alkyl, benzyl, aryl, and heteroaryl thiols or disulfides. Furthermore, kinetic and other additional studies were performed in an attempt to clarify the mechanism of this electrochemical reaction.